Increased prevalence of Parkinson's disease in soils with high arsenic levels - Lee, Chien-Pang; Zhu, Chia-Hsin; Su, Che-Chun (Parkinsonism & related disorders, 2021)
Exposure to arsenic (As)-containing pesticides was associated with an increased risk for Parkinson's disease (PD). Arsenic also induced in murine brains α-synuclein aggregates, a pathognomic feature of PD. People living on farms irrigated with high As water in Taiwan are likely exposed to increased As. We addressed whether increased farm soil As levels correlate with an increased PD risk. We used the information from several national surveys (1983–1986) on soil metal contents to study the relationships between soil metal contents and PD prevalence in Taiwan. PD prevalence (2009–2013) was calculated with a database from Taiwan's compulsory national health insurance. A patient is defined by a PD diagnosis and prescriptions of Levodopa in three or more office visits in twelve months. We used regression models to study the correlation between PD prevalence and soil metal contents. The PD prevalence ranged from 83 to 213 per one hundred thousand persons in different regions of Taiwan. Among the studied heavy metals, we found only As was significantly associated with the PD prevalence. The top three regions (Yunlin, Chiayi, Tainan) in the PD prevalence list correspond exactly with the top three in soil As levels. Soil As levels and PD prevalence had a strong correlation (r = 0.75). PD prevalence is statistically correlated with farm soil As levels in Taiwan. [Display omitted] •Arsenic (As) induced α-synuclein aggregates in murine brains and associated with an increased risk for Parkinson's disease (PD).•If increased environmental As exposure from farm soils is associated with an increased risk for PD?•Farm soil As levels and PD prevalence had a strong correlation (r-value 0.75).•This study confirms that increased farm soil arsenic (As) levels are correlated with an increased PD prevalence in Taiwan.